FIRST MINISTER (PRIME MINISTER) OF THE FIFTH FRENCH REPUBLIC - BETWEEN THE SIGNIFICANT CONSTITUTIONAL POSITION AND THE PREVAILING PRACTICE IN THE SHADOW OF THE HEAD OF STATE - Rapajic, Milan M (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
One of the characteristics of the system of government in the Fifth French Republic is the strengthened position of the head of state, but also the existence of the first minister as a constitutional category with a significant role. The constitution provides the political responsibility of the government with the prime minister and ministers before parliament. Certain French writers have opinion that the Prime Minister appears as the central figure of the constitutional structure. The Prime Minister shall direct the actions of the Government.This is 21 od Constitution. Also, there are specific powers that put the prime minister in the position of its real head of government. Among the prime minister's most important powers is his right to elect members of the government. It is the right to propose to the President of the Republic the appointment but also the dismissal of members of the government. The Prime Minister is authorized to re-sign certain acts of the President of the Republic. In case of temporary impediment of the head of state, the prime minister chairs the councils and committees for national defense, as well as the Council of Ministers. The paper analyzes the constitutional provisions that lead to the conclusion that the position of the Prime Minister is institutionally constructed as strong. Political practice, with the exception of periods of cohabitation, has indicated that most prime ministers have been overshadowed by mostly powerful heads of state. For that reason, it is necessary to analyze the political practice of all eight presidential governments. A review of the already long political life that has lasted since 1958. points to the conclusion that in its longest period, presidents of the republic dominated the public political scene. The prime minister has a more pronounced role in the executive branch during cohabitation periods. However, nine years in three cohabitations cannot change the central conclusion of this paper that the dominant political practice of the Fifth Republic has led to the Prime Minister being essentially in the shadow of the head of state.
Keywords: First Minister of the Fifth French Republic; government organization; head of state; semi-presidential system; Constitution; political practice